Chemo- and regioselective synthesis of polysubstituted 2-aminothiophenes by the cyclization of gem-dibromo or gem-dichloroalkenes with β-keto tertiary thioamides. Issue 38 (23rd September 2020) - Zhang, Xuxue; Liu, Chuan; Deng, Yupian; Cao, Song
Abstract : A facile and practical method for the synthesis of 2, 3, 4-trisubstituted 2-aminothiophenes by the cyclization of gem -dibromoalkenes or gem -dichloroalkenes with β-keto tertiary thioamides has been developed. Abstract : A facile and practical method for the synthesis of 2, 3, 4-trisubstituted 2-aminothiophenes by the cyclization of gem -dibromoalkenes or gem -dichloroalkenes with β-keto tertiary thioamides has been developed. The cyclization reaction proceeded chemoselectively and regioselectively under metal-catalyst-free conditions, providing various structurally diverse 2, 3, 4-trisubstituted N, N ′-dialkyl 2-aminothiophenes in good to excellent yields.